2015
DOI: 10.1002/smll.201502202
|View full text |Cite
|
Sign up to set email alerts
|

CXCR‐4 Targeted, Short Wave Infrared (SWIR) Emitting Nanoprobes for Enhanced Deep Tissue Imaging and Micrometastatic Cancer Lesion Detection

Abstract: Realizing the promise of precision medicine in cancer therapy depends on identifying and tracking of cancerous growths in order to maximize treatment options and improve patient outcomes. However, this goal of early detection remains unfulfilled by current clinical imaging techniques that fail to detect diseased lesions, due to their small size and sub-organ localization. With proper probes, optical imaging techniques can overcome this limitation by identifying the molecular phenotype of tumors at both macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 50 publications
5
72
0
Order By: Relevance
“…These NPs can target subtissue microlesions in a lung metastatic model of breast cancer. [28] Bone-binding molecules have been used to target bone metastasis. The bisphosphonates such as alendronate and zoledronate have high affinity towards the hydroxyapatite and thus have been conjugated on NPs [29, 30] NPs modified with bisphosphonates showed enhanced bond binding in vitro and in vivo, and high bone marrow uptake in bone metastasis of breast cancer cells (MDA-MB-231) in mice.…”
Section: Nanoparticles For Targeting and Imaging Of Breast Cancer mentioning
confidence: 99%
See 1 more Smart Citation
“…These NPs can target subtissue microlesions in a lung metastatic model of breast cancer. [28] Bone-binding molecules have been used to target bone metastasis. The bisphosphonates such as alendronate and zoledronate have high affinity towards the hydroxyapatite and thus have been conjugated on NPs [29, 30] NPs modified with bisphosphonates showed enhanced bond binding in vitro and in vivo, and high bone marrow uptake in bone metastasis of breast cancer cells (MDA-MB-231) in mice.…”
Section: Nanoparticles For Targeting and Imaging Of Breast Cancer mentioning
confidence: 99%
“…These NPs are able to detect subtissue microlesions. [28] Using a similar NIR second window (NIR-II) fluorescent imaging (808 nm laser excitation and 900–1100 nm emission), the single-walled carbon nanotubes are able to visualize both the primary tumor and the sentinel lymph node metastasis in mice. [33] Considering much more tissue depth in human than in small animals, the translation of NIR imaging into clinical practice may be limited to surgery guidance but not body-scale imaging.…”
Section: Nanoparticles For Targeting and Imaging Of Breast Cancer mentioning
confidence: 99%
“…Over the last decades, the optical tissue transparency window in NIR‐I has been employed for noninvasive optical bioimaging of small animals in biomedical research , advancing the development of imaging guided phototherapy and drug delivery . Quite recently, in addition to the conventional NIR‐I window, two or more optical windows have been identified, namely NIR‐II (~1000‐1350 nm) and NIR‐III or short‐wave IR (SWIR) (~1550‐1870 nm) .…”
Section: Introductionmentioning
confidence: 99%
“…15,17,20,21 We show that the surface charge of RENPs are tunable by modification with PEI coating (RENPs@PEI). PEI, a polycation typically used as a gene-delivery nanosystem, 2325 was used to improve solubility of RENPs.…”
Section: Introductionmentioning
confidence: 91%
“…We have previously shown that RENPs can be rendered biologically safe by encapsulation in albumin nanocomposites 15 and can be targeted for the detection of micrometastatic lesions in multiple organs. 20,21 However, the lack of cationic charge on the surface of the albumin nanocomposites renders them unsuitable for the loading of genetic cargo. In the present study, by the surface modification of RENPs using PEI, we have developed a biologically well-tolerated formulation capable of detecting micrometastatic lesions with excellent signal-to-noise ratios and of carrying genetic cargo on its surface.…”
Section: Introductionmentioning
confidence: 99%